STRATEGI PROMOTIONAL MIX DALAM MEMASARKAN PROGRAM UMRAH PADA PT. BIMALYNDO HAJAR ASWAD KOTA BUKITTINGGI - Mukhlis Mukhlis; Zuwardi Zuwardi (CV. Adiba Aisha Amira, 2023)
This research has a background due to the ineffectiveness of PT. Bimalyndo Hajar Aswad, the city of Bukittinggi in promoting the Umrah program product which is marked by the fact that there are still many ordinary people who do not know what the Umrah programs are, besides that there are still many competitors with competitive prices and a decrease in the number of departures of prospective Umrah pilgrims. The purpose of this research is to find out, analyze, promotional mix strategies in marketing the Umrah program at Pt. Bimalyndo Hajar Aswad, City of Bukittinggi. The method in this research is a qualitative method. This research used data collection techniques in the form of interviews, observation and documentation to find out what the promotion mix is in promoting the Umrah program product. While the data analysis technique used is the SWOT analysis method. Promotion mix used by PT. Bimalyndo Hajar Aswad Kota Bukittinggi is personal selling, advertising, direct market, public relations.